Efficacy and safety of magnetic resonance-guided focused ultrasound treatment for refractory chronic pain of medial knee osteoarthritis. (10th September 2021) - Kawasaki, Motohiro; Muramatsu, Shudai; Namba, Hirofumi; Izumi, Masashi; Ikeuchi, Masahiko; Yaogawa, Shin; Morio, Kazuo; Ushida, Takahiro
Abstract: Objective: To elucidate the efficacy and safety of MRgFUS in the treatment for refractory pain derived from medial knee OA. Methods: Twenty patients with medial knee OA eligible for total knee arthroplasty were included in this prospective, non-controlled study (UMIN000010193). MRgFUS treatment was provided at the site of most severe tenderness around the medial femorotibial joint of each patient under real-time monitoring of temperature. The goal temperature of the targeted bone surface was 55 °C. Numerical rating scale (NRS) worst pain scores, Western Ontario and McMaster Universities osteoarthritis index (WOMAC) scores, EuroQol 5 dimensions index (EQ-5D) scores and pressure pain threshold (PPT) were evaluated before treatment (baseline) and at 1 week and 1, 3, 6, and 12 months post-treatment, respectively. Complications and adverse events were also assessed clinically and radiographically. Results: Treatment response (a 50% or greater decrease in NRS score) was seen in 14 patients (14/19, 73.7%) at 12 months post-treatment. Mean NRS score rapidly decreased at 1 month after treatment and continued to decline through the following 12 months. At final follow-up, mean NRS score was 3.2 ± 1.9, significantly lower than at baseline ( p  = 0.0013). Mean WOMAC and EQ-5D scores also improved significantly from 1 month after treatment. Fifteen patients showed significant sustained increases in PPTs at the sites of most severe tenderness. No serious adverse events were observed during and after treatment. Conclusions: MRgFUS treatments were effective not only for managing refractory pain, but also for improving physical functions without adverse events in elderly patients with medial knee OA.